2006
DOI: 10.1021/cm060277j
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Nanostructure in γ-Al2O3

Abstract: We have applied a local structural technique, atomic pair distribution function (PDF) analysis of powder diffraction data to γ-Al 2 O 3 , to obtain a quantitative structure. Refinements of the PDF support previous findings that nonspinel model representations are more suitable to describe the average structure of γ-Al 2 O 3 , as opposed to the spinel model. Surprisingly, also we find a previously unknown fine-scale nanostructure with a domain size ∼ 1 nm. Modeling suggests that within these nanodomains the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 46 publications
6
103
0
1
Order By: Relevance
“…The pH of the aged suspension was 4.5-5.5. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) showed that the c-Al 2 O 3 surface slowly transforms to a layer of a-Al(OH) 3 (gibbsite) and b-Al(OH) 3 (bayerite) mixture upon hydration, in agreement with previous studies (e.g., Wijnja and Schulthess, 1999;Arai et al, 2001;Paglia et al, 2006;Roelofs and Vogelsberger, 2006;Yang et al, 2007).…”
Section: Batch Sorption Experimentssupporting
confidence: 89%
“…The pH of the aged suspension was 4.5-5.5. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) showed that the c-Al 2 O 3 surface slowly transforms to a layer of a-Al(OH) 3 (gibbsite) and b-Al(OH) 3 (bayerite) mixture upon hydration, in agreement with previous studies (e.g., Wijnja and Schulthess, 1999;Arai et al, 2001;Paglia et al, 2006;Roelofs and Vogelsberger, 2006;Yang et al, 2007).…”
Section: Batch Sorption Experimentssupporting
confidence: 89%
“…Using interatomic potentials and first-principles calculations, Paglia et al [19] verified that, in average, over 40% of the cations must occupy nonspinel positions to achieve an accurate structural model while the optimization of spinel-like structural models led to less favorable energies. More recently, a debate in literature [20][21][22][23] about the inability of a nonspinel model to describe the g-alumina bulk and other publications stating just the opposite [12,19,24], leaves some doubts about which model to choose when the goal is to simulate surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…3, showing a platy and rhombus form with dimensions 24 nm (length) Â 16.5 nm (width) Â 6.4 nm (thickness). Similar modelling for the g-Al 2 O 3 samples (D500 and D800) was not possible due to higher degree of disorder in this phase [33,34]. For these samples, the broad diffraction peaks do not only result from coherent scattering of small size domains, but also from lower crystallinity of the crystallites [35].…”
Section: Resultsmentioning
confidence: 84%